The European Economic Constitution. Observations on the Conceptual History of an Unworkable Idea - Joerges, Christian (Cultura giuridica e diritto vivente, 2020)
[La costituzione economica europea. Osservazioni sulla storia di un’idea irrealizzabile] This essay deals with the development of the integration project in the light of Polanyi’s insights, first, with its so-called formative phase. Thereafter it addresses the post-foundational phase, which was characterized by enormous efforts to transform Europe’s economy into a “highly competitive social market economy”. Finally, it deals with the consummation of market integration by the establishment of Monetary Union. The monetary Union included an erosion of the notion of rule-oriented economic governance and, more drastically, the replacement of the economic constitution by emergency governance. A Governance that represents a technocratic exercise or a praxis that escapes the quest for democratic legitimacy and the constraint of the rule of law.